Analysis of Basic Education Policies are Based on Philosophical, Sociological, Political and Economic Foundations - Hartono, Rudi; Ida Bagus Putu Arnyana; Nyoman Dantes (International Journal of Contemporary Studies in Education, 2023)
The process of analyzing policy developments against a background of philosophical, sociological, political and economic foundations will serve as a reference in making policies related to basic education. Education in Indonesia often experiences polemics which are the result of mistakes in taking virtue. The policy emerged from government actors. That way, policy makers and stakeholders are expected to be able to think about, describe, and identify policies taken based on philosophical, sociological, political, and economic foundations. This research departs from field observations so that various solutions are obtained. With various factual data sources as a support in compiling scientific work and obtaining data from scientific literature such as journals and reading books using library research methods. The analysis uses a qualitative research approach; data collection techniques with observations in schools and literature studies. Focus on policy development objectives based on philosophical, sociological, political and economic foundations. Because policies can affect the learning process and the implementation of effective learning. Thus, it is necessary to analyze good educational policies, so that noble ideals can be realized in accordance with the mandate of the 1945 Constitution, namely the intellectual life of the nation.